A comparative analysis of supply chain factors impacting COVID-19 vaccine security in high-income countries (HICs) and low-income and middle-income countries (LMICs) - Jeremy H Veillard; David Klein; Adalsteinn Brown; Manveen Puri (BMJ Global Health)
Introduction The COVID-19 pandemic focused attention on the importance of vaccine security to national security. Demand for vaccines far exceeded supply when the first COVID-19 vaccines were released. Growing data suggest a non-perfect correlation among vaccine development, production, purchases, deliveries and vaccination rates. As such, the best approach to strengthening vaccine security remains unclear. In this study, we use an operations research/operations management framework to characterise the relationship between vaccine security and key supply chain predictor variables in high-income countries (HICs) and low-income and middle-income countries (LMICs).Methods We performed a comparative analysis of vaccine security against eight supply chain variables in a purposive sample of five HICs and five LMICs during the early phase of the pandemic (31 March 2021 and 30 April 2021). All data were obtained from publicly available databases. We used descriptive statistics to characterise our data, basic statistics to compare data and scatter plots to visualise relationships.Results Our data show greater vaccine security in HICs compared with LMICs (32.2% difference in April 2021; 95% CI 4.2% to 60.3%, p=0.03). We report a significant difference between HICs and LMICs in only two of the eight predictor variables studied. Interestingly, we observed large variation in vaccine security within HICs, with Canada, Israel and Japan being frequent outliers, and within LMICs, with India standing out.Conclusion Our data suggest a stronger relationship between vaccine security and ‘downstream’ supply chain variables compared with ‘upstream’ variables. However, multiple outliers and the lack of an even stronger relationship suggests that there is no magic bullet for vaccine security. To boost vaccine resilience, countries must be well governed and strategically reinforce deficient aspects of their supply chains. Modest strength in multiple domains may be the best approach to counteracting the effect of an unfamiliar, novel pathogen.